Extreme Learning of Programming – A Methodology Based on eXtreme Programming for Programming Teaching-Learning - Faria, Eustáquio São José de (2010)
The present work has been developed intending to propose the usage of collaborative practices in teaching programming in such disciplines. A methodology for programming teaching-learning named eXtreme Learning of Programming – XLP has been developed. The methodology is based on an agile methodology known as eXtreme Programming (XP) and on a Cognitive Programming Model. To justify the usage of this methodology, it is well known that the application of Pair Programming contributes to the increase of students’ permanence in computer courses or alike due to motivation, sense of responsibility, and knowledge sharing provided by the social-cognitive conflict obtained from the pairings. Empirical researches are being done in an Information Systems course. Partial obtained results can be seen at the end of the paper.